(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s multicultural world, Iranian cinema is undoubtedly one of the most important tools which its analysis and study can pave the way for different sociological and cultural research, in particular from the perspective of communication and cinema. In a comprehensive view on Iranian cinema from the Constitutional period to the post Islamic Revolution of Iran, in the other words, since cinema entered Iran and the techniques of this industry became popular among filmmakers and numerous audiences were attracted to the cinema’s white screen, until the great happening of the Islamic Revolution of Iran that changed everything including cinema, this study will analyze the nature of cinema, especially in the field of morality and individual values which also shows its impact in the society. In this article, we will observe that before the revolution the body of cinema based on the box office and it was under the influence of the cinema with slangy and entertaining limited themes. With the emerge of the Islamic Revolution, under the influence of the surrounded social conditions, it shifts to the religious and ideological themes which tries to demonstrate the role of society and the government in creating a spiritual revolution in the form of cinema.